(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The pervasive influence of social media on youth mental health has become a critical area of concern, particularly regarding its role in suicide ideation and prevention. This article, Digital Echoes: The Impact of Social Media on Suicide Ideation and Prevention Among Youth, explores the complex duality of social media as both a risk factor and a potential tool for intervention. Drawing from recent empirical studies, psychological theories, and digital behavior analysis, the paper examines how exposure to cyberbullying, idealized portrayals of life, and harmful content can contribute to increased feelings of isolation, anxiety, and suicidal thoughts among adolescents. Conversely, it also highlights how online platforms have been used effectively to disseminate mental health resources, foster peer support networks, and enable early detection of at-risk individuals through algorithmic monitoring. The study discusses the psychological vulnerabilities of youth that make them particularly susceptible to the negative impacts of online environments, including social comparison, fear of missing out (FOMO), and emotional dysregulation. It also reviews successful digital interventions, such as helpline integrations, AI-driven content moderation, and influencer-led mental health campaigns. The article calls for a balanced approach to digital literacy education, improved mental health support within online spaces, and collaboration between tech companies, educators, and mental health professionals. Ultimately, it underscores the importance of creating safe, supportive, and responsive digital environments to mitigate suicide risks and harness the positive potential of social media in youth suicide prevention efforts. The article concludes with policy recommendations and strategies for integrating social media into broader suicide prevention frameworks.